Modelling and active control of the Vacuum Infusion Process for composites manufacture - Modi, Dhiren (2008)
Vacuum infusion technology, even though first reported more than 50 years ago, was not popular for mainstream fibre reinforced polymer composites manufacturing until recently. Its present-day popularity is due to the increasing emphasis on the manufacturing cost as well as environmental and health concerns. As a result, novel processes such as Vacuum Infusion (VI) and Seemans' Composite Resin Injection Moulding Process (SCRIMPTM), employing the same basic technology, have been developed. As latecomers, these processes have not been investigated in detail and there exists a lack of understanding that can undermine the potential improvements in composites manufacturing offered by them. The present work is focused on (i) enhancing the fundamental understanding, and (ii) advancing the processing technology to fully exploit their potential.